Understanding and influencing agency and behavior change in agroecological transformation processes - Alary, Véronique; Baudron, Frédéric; Beltran, Marcela; Falk, Thomas; Freed, Sarah; Guettou Djurfeldt, Nadia; Lestrelin, Guillaume; Singh, Sonali; Zingwena, Taurai (CGIAR System Organization, 2022)
The Agroecology initiative’s Work Package 5 supports behavior change research and engagements in the global network of Agroecological Living Landscapes, working from the basic notion that diverse behavioral changes are required to foster an agroecological transformation. Behavior can refer to actions, interactions, and diverse practices. This means that diverse interacting actors may need to change how they are currently doing different things. Individual and collective behavioral change intensively interacts with individual and/or collective actors’ ability to make important decisions and to act upon them (their Agency). Attention to agency can illuminate influential behavioral drivers that may enable or impede behavior change. This directly leads to a critical challenge faced by many actors who try to trigger agroecological transformation: How can behavioral change and agency critical for agroecological transformation be supported?